Exploring Motivation, Discipline, and Self-Efficacy in Arabic Language Learning at Madrasah Tsanawiyah in Batam City: A Multiple Case Study - Nunuk Sisharwati; Abdul Talib Bin Bon (Badan Litbang dan Diklat Kementerian Agama RI, 2025)
This study explores how motivation, discipline, and self-efficacy shape the Arabic language learning experiences of Madrasah Tsanawiyah (MTs) students in Batam City. Using a qualitative, multiple-case study design, the research was conducted at MTs Bina Ummah and MTs Hang Nadim. Data were collected through in-depth interviews, classroom observations, and document analysis, and were examined using the interactive analysis model proposed by Miles and Huberman. The findings reveal that students’ learning motivation is constructed through two primary contexts: religious meaning and digital learning experiences. At MTs Bina Ummah, Arabic learning is perceived as an integral part of religious practice, which strengthens students’ learning commitment and perseverance. In contrast, at MTs Hang Nadim, motivation develops through the use of interactive digital media that promotes active student engagement. Learning discipline shifts from rule-based compliance toward reflective self-discipline, particularly when students are entrusted with greater responsibility for managing their own learning. Self-efficacy grows through continuous teacher support and incremental experiences of success, fostering students’ confidence to participate and communicate in Arabic. Rather than defining learning outcomes solely in terms of academic achievement, this study conceptualizes outcomes qualitatively as students’ perceived learning success, sustained engagement, learner autonomy, and increased self-confidence. Conceptually, the findings demonstrate that the dynamic interaction of motivation, discipline, and self-efficacy forms a meaningful Arabic language learning system within the spiritual and digital contexts of madrasah education AbstrakPenelitian ini bertujuan mengeksplorasi bagaimana motivasi, kedisiplinan, dan efikasi diri membentuk pengalaman belajar bahasa Arab siswa Madrasah Tsanawiyah (MTs) di Kota Batam. Penelitian menggunakan pendekatan kualitatif dengan desain studi kasus ganda yang dilaksanakan di MTs Bina Ummah dan MTs Hang Nadim. Data dikumpulkan melalui wawancara mendalam, observasi pembelajaran, dan analisis dokumentasi, kemudian dianalisis menggunakan model interaktif Miles dan Huberman. Hasil penelitian menunjukkan bahwa motivasi belajar siswa bersumber dari dua konteks utama, yaitu makna religius dan pengalaman pembelajaran digital. Di MTs Bina Ummah, pembelajaran bahasa Arab dipersepsikan sebagai bagian dari praktik keberagamaan, sehingga memperkuat komitmen belajar dan ketekunan siswa. Sementara itu, di MTs Hang Nadim, motivasi tumbuh melalui pemanfaatan media digital yang interaktif dan mendorong keterlibatan aktif siswa. Kedisiplinan belajar mengalami pergeseran dari kepatuhan berbasis aturan menuju kesadaran reflektif, terutama ketika siswa diberi kepercayaan untuk mengelola tanggung jawab belajarnya. Efikasi diri berkembang melalui dukungan guru dan pengalaman keberhasilan bertahap, yang meningkatkan keberanian siswa untuk berpartisipasi dan berkomunikasi dalam bahasa Arab. Penelitian ini memaknai hasil belajar tidak semata sebagai capaian akademik, tetapi sebagai persepsi keberhasilan belajar, keterlibatan berkelanjutan, kemandirian belajar, dan peningkatan kepercayaan diri. Secara konseptual, temuan ini menegaskan bahwa interaksi antara motivasi, kedisiplinan, dan efikasi diri membentuk sistem pembelajaran bahasa Arab yang bermakna dalam konteks spiritual dan digital madrasah